Raising Public Awareness in Preserving Historical Heritage Sites Of Patah Sembilan Stone in Langkah Serentak Limbai Seayun Land - Purnama, Boby Yasman; Wulandari, Dea Nanda; Rose, Julia (The Islamic Education and Multiculturalism Foundation, 2022)
This journal aims to examine the historical events or relics that developed in the Senamat Ulu Village, Bathin III Ulu Sub-district, Muaro Bungo Regency, Jambi Province. This article uses historical methods by library research, including archival studies, observations and interviews with related sources. Departing. From the history, uses with make sense and conscience things to know the history around us, the existence of the Batu Patah Sembilan historical become the tools to tell the importance of the presence of this site in the birth of civilization on Earth